Variabilidade produtiva, tamanho de parcela e uso de bordaduras em experimentos com culturas olerícolas em ambiente protegido - Santos, Daniel (2016)
The work aimed to study the variability in protected environments cultivated with zucchini, lettuce, green bean, peppers and cherry tomatoes and test the use of borders and the handling of the plot size is effective in minimizing the variability in these experiments . In the study we used uniformity of test data in plastic greenhouse, which were as follows: two experiments with zucchini five with lettuce, three with green bean, two with chili and one with cherry tomatoes. In the analysis considered the existence of parallel rows of growing the lateral openings of the oven and columns perpendicular to these openings. Different settings were created by deleting lines and columns for generating the borders and also with the use of different sizes portion. For each setting performed a variance homogeneity test between the remaining lines and columns, and to calculate a general coefficient of variation. There is variability between rows and between columns in experiments with zucchini, lettuce, green bean and pepper in plastic greenhouse. The use of the lateral borders of plastic greenhouse is no benefit in terms of reduced coefficient of variation or reduction of the cases of variability between rows or columns. The use of a plot size equal to or more than two plants in experiments with zucchini, lettuce, green bean, and a plot size equal to or greater than ten plants for sweet pepper, provides homogeneity of variance between lines and columns.